Zubay's Principles of Biochemistry - Veer Bala Rastogi; K.R. Aneja (New Delhi Medtech, 2017)
Principles of biochemistry has been prepared by three distinguished authors of Chemistry/Biochemisty known for their academic excellence and pedagogical approach in teaching the subject at graduate and post graduate level. Biochemistry is now cosidered to be one of the fundamental subjects for various bioscience courses. A number of Indian universities have begun to include it in their undergaduate and postgraduate programmes. The subject of biochemistry works at molecular level and thus brings to light the hidden secrets of life. The rapid development and enormouss expansion of every phase of biochemistry has not only markedly enriched our knowledge about the nature of life but has also made biochemistry the language of life. In planning this book, our challenge has been to incorporate details of all recent developments whilst retaining our original aim, namely to concentrate on those techniques and principles which underlie practical exercises that undergraduates in all the biological sciences can expect to encounter in their practical classes and to cover in less detail the more sophisticated techniques that have made possible the advances they will learn about in their lectures and associated reading. Students face problems in conceptualizing the subject within a limited time. Most of the students need a book that is lucidly presented, orderly arranged and profusely illustrated. The present book has been written in simple language in such a way that a student with very little chemistry background can easily follow the various aspects of biochemistry presented in the book. the book matches what best is availabe in the standard textbooks in the subject including those by Stryer, Devlin, Griffith, and Lehniger in their books on the subject. This profusely illustrated book covering syllabi of most of the universities of India and abroad should be an ideal text-cum-reference book for easy comprehension of the subject. At the end of the book glossary of common terms used in biochemistry have been provided. Student activity in the form of reiew problems has been provided with each chapter.
Keywords: Biochemistry. Protein Structure and Function. Enzymes. Photosynthesis. Gene Cloning. Next- Generation DNA Sequencing